Curricular training report in a contract research organization (CRO) - Alves, Sandra Isabel Rodrigues (2015)
This report describes my experience as a trainee at W4Research, a national Contract Research Organization (CRO). This internship intended to put into practice the skills acquired during the curricular year of the Master in Pharmaceutical Biomedicine. This professional context experience has allowed me to perform activities especially in the implementation of a quality management system and also in medical writing. I was also involved in the design of two observational studies and one socioepidemiological study, and in a clinical trial site feasibility.